2019
DOI: 10.1159/000499044
|View full text |Cite
|
Sign up to set email alerts
|

The Heterogeneous Pathogenesis of Selective Immunoglobulin A Deficiency

Abstract: Selective immunoglobulin A deficiency (SIgAD) is the most prevalent type of primary immunodeficiency disorder. The phenotypic feature of SIgAD is related to a defect in B lymphocyte differentiation into plasma cell-producing immunoglobulin A (IgA). In this review, we summarize the recent advances in this regard. Genetic (including major histocompatibility complex [MHC] and non-MHC genes), immunologic (including B and T lymphocyte subsets abnormality), cytokines/chemokines and their related receptors, apoptosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 133 publications
1
13
0
Order By: Relevance
“…However, a fundamental defect in SIgAD seems to be impaired maturation of IgA-bearing B-cells into IgA-secreting plasma cells [ 29 ]. Moreover, studies have proven that IgA-deficient patients have defects in the process of IgA class switching recombination (CSR), production, as well as secretion of IgA, and long-term survival of IgA-switched memory B-cells and plasma cells, possibly due to an increased rate of apoptosis [ 30 , 31 , 32 ]. The latter leads to a paucity of B-cells secreting IgA both in the plasma and GI tract mucosa, in contrary to a healthy population [ 33 , 34 ].…”
Section: Selective Immunoglobulin a Deficiencymentioning
confidence: 99%
See 4 more Smart Citations
“…However, a fundamental defect in SIgAD seems to be impaired maturation of IgA-bearing B-cells into IgA-secreting plasma cells [ 29 ]. Moreover, studies have proven that IgA-deficient patients have defects in the process of IgA class switching recombination (CSR), production, as well as secretion of IgA, and long-term survival of IgA-switched memory B-cells and plasma cells, possibly due to an increased rate of apoptosis [ 30 , 31 , 32 ]. The latter leads to a paucity of B-cells secreting IgA both in the plasma and GI tract mucosa, in contrary to a healthy population [ 33 , 34 ].…”
Section: Selective Immunoglobulin a Deficiencymentioning
confidence: 99%
“…Many authors suggested a role of impaired T-cell function in the development of SIgAD, as possibly defective antibody production or secretion may be due to dysfunction or decreased activity of different subpopulations of T-cells [ 30 , 36 ]. However, most of the studies concerning the role of T-cells in the pathogenesis of SIgAD are inconclusive.…”
Section: Selective Immunoglobulin a Deficiencymentioning
confidence: 99%
See 3 more Smart Citations